The analysis of code switching found in padang bulan novel by andrea hirata - Inten, I Gusti Ayu; Ariyaningsih, Ni Ny Deni; Jendra, I Md Iwan Indrawan (Institut Pariwisata dan Bisnis Internasional, 2020)
Nowadays, phenomenon of combining two languages in communication process often occurred in bilingual community called code switching. This study concerned with code switching used by novelist Andrea Hirata in his utterance in Padang Bulan novel. This study aimed to answer (1) What types of code switching are used in the novel, and (2) What reasons are for the code switching found in the novel. A descriptive qualitative method was used. The method was applied by Appel and Muysken (1987) to classify the types of code switching and the theory by Hoffman (1991) to analyze the reasons for code-switching. The result shows that three types of code-switching and three reasons for code-switching were found. First, the three types of code-switching are namely tag switching, intra-sentential switching, and inter-sentential switching, in which the most dominant switching is inter sentential. Second, Three reasons for code-switching were talking about a particular topic, being emphatic about something, quoting somebody else, and expressing group identity. The most dominant reason is talking about a particular topic.